NAǴIS ELEMENTLERIN SIZIP ÚYRETIW USÍLLARÍ - Amanbaev, M.A.; Smaylova, G.Y. (SCIENCE and SOCIETY, 2022)
The article explores the craft of painting and develops students' artistic imagination, industriousness. Pattern elements have been studied in artistic painting, decorating decorations and various forms, except for the laws of composition, types of paints used in its painting, their specific properties, types of paints, color scheme.
Keywords: pattern; nationality; color; coloring; student; ornament